1974
DOI: 10.3171/jns.1974.40.3.0376
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure in patients with dementia and communicating hydrocephalus

Abstract: ✓ Intracranial pressure (ICP) was monitored continuously for 48 to 72 hours in 12 patients with dementia and communicating hydrocephalus, to see if this would help determine which patients might benefit from surgical shunting of CSF, since not all such patients respond to treatment. Patients who showed variability of ICP improved following surgery, while patients with consistently flat ICP tracings did not. It is suggested that continuous monitoring of ICP may help identify cases suitable for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…This finding accords with reports (Chawla et al, 1974;Symon and Dorsch, 1975;Lamas and Lobato, 1979;Borgesen and Gjerris, 1982;Kosteljanetz, 1986;Tans and Poortvliet, 1989;Malm et al, 1995) that groups of patients with 'normal pressure hydrocephalus' have a higher CSF pressure and a higher resistance to CSF absorption than either normal subjects or patients with degenerative neurologic disease. However, the mean difference between hydrocephalic and non-hydrocephalic patients is sufficiently small, relative to the range of variation of pressure and resistance among normals, that pressure and resistance measurements do not infallibly predict response to surgical shunting.…”
Section: 3supporting
confidence: 80%
“…This finding accords with reports (Chawla et al, 1974;Symon and Dorsch, 1975;Lamas and Lobato, 1979;Borgesen and Gjerris, 1982;Kosteljanetz, 1986;Tans and Poortvliet, 1989;Malm et al, 1995) that groups of patients with 'normal pressure hydrocephalus' have a higher CSF pressure and a higher resistance to CSF absorption than either normal subjects or patients with degenerative neurologic disease. However, the mean difference between hydrocephalic and non-hydrocephalic patients is sufficiently small, relative to the range of variation of pressure and resistance among normals, that pressure and resistance measurements do not infallibly predict response to surgical shunting.…”
Section: 3supporting
confidence: 80%
“…Air encephalography, isotope or metrizamide cisternography, measurement of cerebral blood flow (CBF), CSF-tap-test, long term intracranial pressure (ICP) monitoring and a different set of hydrodynamic studies and pressure/volume tests have been carried out with variable results 6' s, 9, H, 13, 15, 25,27,37,41,43,48,52,56,59,62 ICP monitoring and hydrodynamic studies have been widely reported in NPH syndrome. Normal or low ICP, with high or low amplitude beta waves and sometimes plateau waves especially during REM sleep have been reported as typical of NPH and clearly related with a good outcome 6-9' 13,16,17,27,35,37,42,49,59 Nevertheless, the value of long term ICP monitoring and/or CSF studies in order to select candidates to shunt is still controversial 7' 52 The sensitivity and specificity of ICP monitoring and CSF dynamics have not been defined yet. In general, a better knowledge of the different forms of' NPH is still necessary to get a better understanding of the natural evolution, clinical symptoms and signs and possible outcome in this important group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, the syndrome of Normal Pressure Hydrocephalus (NPH) was completely outlined by Hakim and Adams in 1965 ~ ' 2, 29, 30. A Normal Pressure Hydrocephalus Syndrome (NPHS) can be idiopathic or secondary to subarachnoid haemorrhage, head injury, aqueductal stenosis, intracranial surgery and many other aetiologies 1, 2, 7, 13,29,30,34,36,59,63 From the clinical point of view, the diagnosis of NPHS is considered in those patients with gait disturbance, progressive dementia and urinary or faecal incontinence ~, 2, ~2, 34,52. Although the complete triad is perhaps the most frequent clinical presentation, incomplete and atypical forms of the syndrome have been reported13, 14,19,36,48,52,57,59 In spite of its apparent simplicity, NPH syndrome is a clinical complex entity, with incomplete physiopathological knowledge and too often contradictory opinions about its proper management.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been discovered that patients with fluctuat ing intracranial pressure show significantly better response to surgery than those with 'flat curves' [18,20]. Assuming that the fall ing spells are indeed caused by a hydroce phalic crisis as suggested by Adams et al [1], the good response to shunting in our 2 pa tients suffering from falling spells could be explained.…”
Section: Discussionmentioning
confidence: 62%
“…Sudden falls have also been described in association with colloid cysts of the third ventricle [15], obstructive hydrocephalus due to tumor in the floor of the fourth ven tricle [16], and aqueduct stenosis [17], Continuous intracranial pressure moni toring in NPH patients has demonstrated that there are often periods with elevated intraventricular pressure [18][19][20][21][22]. It has also been discovered that patients with fluctuat ing intracranial pressure show significantly better response to surgery than those with 'flat curves' [18,20].…”
Section: Discussionmentioning
confidence: 99%